Stimulation of phagocytes by Lactobacillus strains in immunocompromised hosts - Villena, Julio Cesar (2010)
We evaluated the effect of different probiotic Lactobacillus (Lb) on the number and activity of phagocytic cells in mice immunosuppressed by cyclophosphamide (Cf). Lb rhamnosus CRL1505 (LR5), Lb rhamnosus CRL1506 (LR6) and Lb casei CRL431 (LC) were selected previously in immunocompetent mice. Adult mice were administered LR5, LR6 or LC. After each treatment, these groups and control mice (C) received an intraperitoneal (ip) injection of Cf (150 mg/kg) and were sacrificed at different times post-chemotherapy (for 15d). We studied: a) peritoneal macrophages (PMf) phagocytic activity, b) neutrophil number and peroxidase activity (Px) in blood, c) expression of Gr-1 in blood by flow cytometry, and d) Candida albicans (Ca) clearance after an ip challenge. Mice treated with the Lb strains showed a higher PMf activity when compared with the C group (P <0.05). Cf induced severe neutropenia and reduced the number of Px+ and Gr-1+ cells in blood. LC, LR5 and LR6 groups showed a less pronounced decline and earlier recovery of blood neutrophils, Px+ and Gr-1low cells (P<0.05). In addition, treatments with Lb increased the resistance to Ca challenge, since in these groups, Ca counts in infected tissues were lower than in the C group (P<0.05). Preventive administration of probiotic Lb strains is able to stimulate phagocytic cells in immunocompromised hosts. The improvement of phagocytes activity would be able to increase resistance to infections.